Runting and Stunting Syndrome Is Associated With Mitochondrial Dysfunction in Sex-Linked Dwarf Chicken - Li, Hongmei; Hu, Bowen; Luo, Qingbin; Hu, Shuang; Luo, Yabiao; Zhao, Bojing; Gan, Yanmin; Li, Ying; Shi, Meiqing; Nie, Qinghua; Zhang, Dexiang; Zhang, Xiquan (Frontiers in Genetics, 2020)
Runting and Stunting Syndrome (RSS) in chicken are commonly known as "frozen chicken". The disease is characterized by lower body weight, slow growth and the incidence rate is widely 5% - 20% in sex-linked dwarf (SLD) chickens. However, the etiology of RSS in chickens has plagued researchers for several decades. In this study, histopathology studies demonstrated that the hepatocytes of the RSS chickens contain many mitochondria with damaged and outer and inner membrane along with vacuolar hydropic degeneration. No mtDNA mutation was detected, but our microarray data showed that RSS chickens exhibited abnormal expression of genes, many of which are involved in oxidative phosphorylation (OXPHOS) and fatty acid metabolism. In particular, nuclear gene IGF2BP3 was up-regulated in RSS chickens’ liver cells. The abnormal expression of these genes is likely to impair the OXPHOS, resulting in reduced ATP synthesis in the hepatocytes of the RSS chickens, which may in turn leads to poor weight gain and retarded growth or stunting of chicks. Our findings suggest that mitochondria dysfunction rather than chronic inflammation is responsible for the reduced growth and RSS in SLD chickens. Mutations in GHR have been shown to compromise mitochondrial function in SLD chickens. Since the mitochondrial damage in the RSS chicken is more severe, we suggest that extra genes are likely to be affected to exacerbate the phenotype.